1992
DOI: 10.1007/bf00232386
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis in protoplast derived calli of cultivated jute, Corchorus capsularis L.

Abstract: Protoplasts were isolated from cotyledon, hypocotyl and mesophyll cells of Corchorus capsularis L., a major fibre crop, by one step enzyme digestion method. They were further cultured successfully on modified KM-8p (Kao and Michayluk, 1975) medium to form microcalli. The required cultural conditions could be used to achieve 34% to 78% plating efficiency, depending upon the source of protoplasts. Hypocotyl protoplasts gave the highest plating efficiency. On transfer to regeneration medium, somatic embryos devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
1
14
1
Order By: Relevance
“…Protoplasts derived from cotyledonary tissue of C. capsularis cv. JRC 321' and hypocotyl protoplasts of C. olitorius cv.`JRO 878' were prepared following the method of Saha and Sen (1992). Fusions between anthocyanin-pigmented, red-coloured protoplasts derived from hypocotyls of`JRO 878' of C. olitorius, and green-coloured cotyledonary leaf protoplasts of C. capsularis cv.`JRC 321' were carried out.…”
Section: Methodsmentioning
confidence: 99%
“…Protoplasts derived from cotyledonary tissue of C. capsularis cv. JRC 321' and hypocotyl protoplasts of C. olitorius cv.`JRO 878' were prepared following the method of Saha and Sen (1992). Fusions between anthocyanin-pigmented, red-coloured protoplasts derived from hypocotyls of`JRO 878' of C. olitorius, and green-coloured cotyledonary leaf protoplasts of C. capsularis cv.`JRC 321' were carried out.…”
Section: Methodsmentioning
confidence: 99%
“…There are reports of somatic embryos obtained from the protoplast derived calli of C. capsularis, which could not be established into plantlets. (Saha and Sen 1992). It was reported earlier that in vitro regeneration in this genus is genotype-dependent and the material is recalcitrant to regeneration .…”
Section: Introductionmentioning
confidence: 93%
“…Attempts to obtain regeneration from hypocotyl and root calluses were made by subculturing on to basic MS medium supplemented with a range of concentrations of BA, zeatin and kinetin, with or without 0.1 and 0.5 mg 1-1 of the aux-ins IAA and NAA, and on the modified MS media of Saha and Sen (1992) and Gawal and Robacker (1990). Attempts to obtain regeneration from hypocotyl and root calluses were made by subculturing on to basic MS medium supplemented with a range of concentrations of BA, zeatin and kinetin, with or without 0.1 and 0.5 mg 1-1 of the aux-ins IAA and NAA, and on the modified MS media of Saha and Sen (1992) and Gawal and Robacker (1990).…”
Section: Regeneration Mediamentioning
confidence: 99%
“…Islam et al (1992) showed that protocols are available to obtain regenerants in some varieties C.capsularis, and Saha and Sen (1992) reported somat-ic embryogenesis from cotyledon and hypocotyl protoplast derived calluses in C.capsularis. Micropropagation would enable the rapid clonal multiplication of improved genotypes of this annual crop and the maintenance of useful genotypes.…”
Section: Introductionmentioning
confidence: 99%